SFPE Handbook of Fire Protection Engineering - Hurley, Morgan J.; Gottuk, Daniel T.; Hall Jr., John R.; Harada, Kazunori; Kuligowski, Erica D.; Puchovsky, Milosh; Torero, Jose´ L.; Watts Jr., John M.; WIECZOREK, CHRISTOPHER J. (Springer New York : Imprint: Springer, 2016)
The definitive reference on fire protection engineering, now expanded to three volumes Available in electronic format for the first time An indispensible source for reliable coverage of fundamentals, fire dynamics, hazard calculations, fire risk analysis, modeling and more SFPE members, please contact SFPE for special discount price.